Anthocyanins and flavonols from the flowers of Amherstia nobilis endemic to Myanmar. (October 2019) - Iwashina, Tsukasa; Tanaka, Nobuyuki; Aung, Mu Mu; Mizuno, Takayuki; Yukawa, Tomohisa
Abstract: Three anthocyanins (1 –3 ) and eight flavonols (4 –11 ) were isolated from the flowers of Amherstia nobilis endemic to Myanmar. Anthocyanins were identified as cyanidin 3- O -glucoside (1 ), 3- O -xyloside (2 ), and peonidin 3- O -glucoside (3 ). On the other hand, flavonols were identified as isorhamnetin 3- O -glucoside (4 ), 7- O -glucoside (5 ), 3, 7-di- O -glucoside (6 ) and 3- O -rutinoside (7 ), quercetin 3- O -rutinoside (8 ) and 3- O -glucoside (9 ), and kaempferol 3- O -rutinoside (10 ) and 3- O -glucoside (11 ). Although an anthocyanin, pelargonidin 3- O -pentoside, has been reported from the flowers of A. nobilis, it was not found in this survey. The presence of flavonols in A. nobilis was reported in this survey for the first time. Flavonoid composition of Amherstia was chemotaxonomically compared with those of phylogenetically related genera Cynometra and Brownea . Highlights: Flower anthocyanins and flavonols of Amherstia nobilis is endemic to Myanmar were surveyed. Three anthocyanins and eight flavonols were isolated and identified as cyanidin 3- O -glucoside and 3- O -xyloside, and peonidin 3- O -glucoside (anthocyanins), and isorhamnetin 3- O -glucoside, 7- O -glucoside, 3, 7-di- O -glucoside, 3- O -rutinoside, kaempferol 3- O -glucoside and 3- O -rutinoside, and quercetin 3- O -glucoside and 3- O -rutinoside (flavonols). Flavonoid profiles of Amherstia nobilis were chemotaxonomically compared with those of related Cynometra and Brownea species.